Fungicides alternatives for pre-flowering linseed - Bruinsma, Gabriel Mathias Weimer; Carvalho, Ivan Ricardo; Pradebon, Leonardo Cesar; Loro, Murilo Vieira; Sarturi, Marlon Vinicius da Rosa; Huth, Caroline (Scientia Agraria Paranaensis, 2022)
Molecule rotation in the control of fungal diseases is essential to ensure sustainability and avoid the tolerance of pathogens to fungicides. Evidencing managements that promote greater efficiency in the control can contribute to increase the efficiency in the control of diseases.This work aims to reveal control alternatives for foliar diseases through different anti-fungal molecules applied in pre-flowering in the linseed crop. The experiment took place in the experimental area of Escola Fazenda, UNIJUÍ, located in the municipality of Augusto Pestana (RS). The experimental design used randomized blocks, with ten fungicide treatments in foliar application and three replications, totaling 30 experimental units. In the useful area of ​​each experimental unit, the following characteristics were measured: plant height, plants per square meter, number of grains per plant, weight of grains per plant, grain yield, normalized green red difference index, green leaf index, spectral saturation index. The data obtained were submitted to descriptive analysis and to the assumptions of analysis of variance, such as homogeneity of residual variances by Bartlett’s test and normality of errors by Shapiro Wilk. Afterwards, analysis of variance was carried out at 5% probability, with the significant variables, Tukey’s test of multiple comparison of means was applied at the level of 5% of probability. In order to identify the tendency of association between the characters, Pearson’s linear correlation was determined at 5% probability by t test. The active ingredient Pyraclostrobin + Fluxapyroxad can contribute favorably to the maintenance of floral units, capsules and grains per plant. The correct positioning of the use of the molecule is decisive and requires further studies in linseed culture.